MOBILE CAMPUS: A REFLECTIVE AND COLLECTIVE DIMENSION OF EDUCATIONAL ACTIVITIES MEDIATED BY MOBILE TECHNOLOGY - Ivan Yu. Travkin (Статистика и экономика)
The author considers a definition and general characteristics of the mobile campus allowing to ensure a combination of informal and social types of the educational activities with formal learning in a traditional educational institution (institutes of higher education). A fundamental element of the mobile campus is intelligent algorithms providing learning analyst for personalized learning experience. Also the article examines connections between the mobile campus and a learning community, a personal learning network and electronic student profile.